Impaired Fixation-Related Theta Modulation Predicts Reduced Visual Span and Guided Search Deficits in Schizophrenia - Dias, Elisa C; Van Voorhis, Abraham C; Braga, Filipe; Todd, Julianne; Lopez-Calderon, Javier; Martinez, Antigona; Javitt, Daniel C (Cerebral cortex (New York, N.Y. 1991), 2020)
Abstract During normal visual behavior, individuals scan the environment through a series of saccades and fixations. At each fixation, the phase of ongoing rhythmic neural oscillations is reset, thereby increasing efficiency of subsequent visual processing. This phase-reset is reflected in the generation of a fixation-related potential (FRP). Here, we evaluate the integrity of theta phase-reset/FRP generation and Guided Visual Search task in schizophrenia. Subjects performed serial and parallel versions of the task. An initial study (15 healthy controls (HC)/15 schizophrenia patients (SCZ)) investigated behavioral performance parametrically across stimulus features and set-sizes. A subsequent study (25-HC/25-SCZ) evaluated integrity of search-related FRP generation relative to search performance and evaluated visual span size as an index of parafoveal processing. Search times were significantly increased for patients versus controls across all conditions. Furthermore, significantly, deficits were observed for fixation-related theta phase-reset across conditions, that fully predicted impaired reduced visual span and search performance and correlated with impaired visual components of neurocognitive processing. By contrast, overall search strategy was similar between groups. Deficits in theta phase-reset mechanisms are increasingly documented across sensory modalities in schizophrenia. Here, we demonstrate that deficits in fixation-related theta phase-reset during naturalistic visual processing underlie impaired efficiency of early visual function in schizophrenia.